2010
DOI: 10.1155/2010/579256
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Popliteal Venous Aneurysm

Abstract: We report a case of a 21-year-old man with a popliteal venous aneurysm of the left popliteal fossa, with local symptoms and pain during palpation. Early diagnosis is fundamental in order to prevent the thromboembolic events or other major complications. Duplex scanning, Computed Tomography scanning, and Magnetic Resonance imaging are considered to be important non-invasive diagnostic methods for the diagnosis of PVA. The Angio Computed Tomography acquisition confirmed a 36 mm × 17 mm oval mass in the left p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Coffman et al reported a case with recurrent sharp and severe pain in the popliteal fossa which was later revealed to be due to PVA [17]. Fiori et al reported a case with local discomfort in the left popliteal fossa during daily activities and palpation [16]. In a meta-analysis knee pain and popliteal mass was reported as the clinical presentation secondary to PVA in 35% of cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…Coffman et al reported a case with recurrent sharp and severe pain in the popliteal fossa which was later revealed to be due to PVA [17]. Fiori et al reported a case with local discomfort in the left popliteal fossa during daily activities and palpation [16]. In a meta-analysis knee pain and popliteal mass was reported as the clinical presentation secondary to PVA in 35% of cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is a very useful imaging method to identify the nature of a cystic or solid mass, and arterial or venous origin, however sometimes it is not sufficient. Fiori et al 3) reported that a popliteal venous aneurysm in the popliteal fossa demonstrated only a mixed echogenicity mass, with no evidence of an arterial or venous nature, using color-Doppler ultrasonography. Tatari et al 7) reported a well-circumscribed mass, resembling a Baker's cyst, using ultrasonography; however, it was finally confirmed to be pigmented villonodular synovitis.…”
Section: Discussionmentioning
confidence: 99%
“… 2) Furthermore, some papers in the literature also report a vascular problem, namely popliteal artery and vein aneurysm, that also present as a popliteal mass. 3) Therefore, careful differential diagnosis of popliteal masses is needed because occasionally popliteal masses require surgical intervention.…”
mentioning
confidence: 99%
“…4,6 Most, however, present with pulmonary embolism (24%) or chronic venous disease (76% limb swelling, post thrombotic symptoms) but present as a popliteal mass, which is not uncommon (26%). 3,5,6…”
Section: Discussionmentioning
confidence: 99%